Exploring Digital Competency as a Fundamental Job Competency in Higher Education - Choi, Seongyune; Jang, Yeonju; Kim, Hyeoncheol (JOIV : International Journal on Informatics Visualization, 2025)
In the era of artificial intelligence, emerging digital technologies have revolutionized the nature of workplaces, making digital competency (DC) an increasingly essential competency in the modern job market. However, there are discrepancies between the existing and required levels of DC among employees, highlighting the need for proper and early educational interventions to foster this competency in higher education. In response to this need, this study aims to explore the degree of commitment (DC) among university students in work contexts. This study first developed an instrument to assess the level of DC and conventionally stressed job competencies—cognitive, interpersonal, and self-leadership—and applied it to 4,297 first-year university students. The study first compared the students' DC levels with other job competencies and found that their DC levels were lower than those of other competencies. Additionally, the study investigated the relationship between DC and other job competencies, identifying the prerequisite role of DC in affecting other competencies. Finally, the study also explored factors that promote DC and found that students' interest in emerging information and communication technologies is the most prominent indicator of their DC level. We also examined the effect of experience and attitude toward learning programming on the DC level and found that they were also significant factors. In particular, learning both block-based and text-based programming languages was the most effective means to improve DC. Accordingly, the practical implications for future studies and stakeholders regarding students' DC in higher education were discussed.